Medullary thyroid carcinoma - Raue, Friedhelm (Springer, 1992)
Medullary Thyroid Carcinoma is a rare thyroid tumor originating from neural crest cells, the C-cell that implies several special features, secretion of different neuroendocrine markers, association with other endocrine tumors and familial appearance. The familial variant of medullary thyroid carcinoma allows an early detection by biochemical and genetic testing. At that stage acceptable surgical treatment will cure the patient. The sporadic form of medullary thyroid carcinoma will be diagnosed in a progressive stage, but adequate surgical procedure can cure these patients too. Long term survival depends on stage, age, sex, and variant of the disease and seems to be as good as in other differentiated thyroid cancers
Keywords: Schilddrüsenkrebs; Medullärer Schilddrüsenkrebs